Analysis of Creative Thinking Skills of Elementary School Students in the Application of the Project-based Learning (PjBL) Model Assisted by Mind Mapping - Nanik Erlia Santi; Fajar Setiawan; Meirza Nanda Faradita (Indonesian Journal of Primary Education, 2025)
This study aims to describe the thinking skills of elementary school students in the application of the project-based learning model assisted by mind mapping using qualitative methods and descriptive approaches. The data sources are teachers and principals from interviews; the activity of implementing PjBL assisted by mind mapping observed in observation, as well as a questionnaire for 9 grade V students of SD Muhammadiyah 14 Surabaya. Fluency in coming up with many ideas and providing many ways can be seen from the students' ideas/ideas that vary in each child. Flexibility in generating ideas can be seen in students' activities when looking for other alternatives to make it easier for them to understand the material. The authenticity in producing new and unique expressions is reflected when looking at new ideas produced by students, for example, the grouping of rare or protected flora and fauna, so that it is not monotonous in the material alone. The details in adding or detailing an idea to make it more interesting are illustrated when students add or detail an object by adding colors, images, and symbols to enrich their understanding. This mind mapping project is able to be an alternative to creating learning strategies for teachers and students